PELATIHAN PEMBUATAN BUAH JAMBU MENJADI OLAHAN ICE CREAM ALA JEPANG - Reny Wiyatasari (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2019)
This service’s activity to society aims to find out introduce the use of guava fruit as a basic ingredient of modern food from Japan, namely mochi ice cream. The method used was socialization and training aimed at the PKK group of Donorojo village, Tretep Temanggung sub-district. This service’s activity to societyis expected to be able to lift the selling value of guava which is one of the agricultural commodities that are often found in Donorojo Village. In addition, through this activity it is hoped that it can also increase people's interest in consuming healthy snacks. This service consists of several steps, namely socialization of guava, nutrition, and mochi; cooking training; and evaluation in the form of creations made by mochi ice cream. Through this evaluation, trainees can channel their creativity through the process they produce.